Effects of project-based learning strategy on self-directed learning skills of educational technology students. - Bagheri, Mohsen; Wan Ali, Wan Zah; Abdullah, Maria Chong; Mohd Daud, Shaffe (Contemporary Educational Technology, 2013)
Given the importance of globalization as well as the need to train skilled and knowledgeable employees for the 21st century workforce, higher education needs to take a more critical look at the educational practices and instructional methods which lead to improvements in students’ essential skills such as self-directed learning. This study sought to examine the effects of project-based learning (PoBL) strategy on students’ self-directed learning skills in a system-based education course offered in the educational technology department of Arak University in Iran. In order to achieve this end, a sample of 78 students in the field of educational technology who enrolled in the system-based education course was selected. Subjects were randomly assigned to one of the two groups: the experimental group (PoBL strategy) and control group (conventional teaching strategy). The self-directed learning readiness scale (SDLRS) was administrated three times (i.e. pretest, post-test one, and post-test two). The experimental group received the PoBL strategy and the control group was exposed to conventional teaching (CT) methods. The results of two-way repeated measure ANOVA tests revealed that students who were taught using PoBL strategy performed significantly better in terms of self-directed learning skills than did students who were taught using CT strategy.